2005
DOI: 10.1002/pssc.200460659
|View full text |Cite
|
Sign up to set email alerts
|

p‐type conducting ZnO: fabrication and characterisation

Abstract: PACS 73.61.Ga, We report on the fabrication of ZnO:N by thermal oxidation of sputter-deposited zinc nitride. Through optimising several technological steps we achieved p-type conductivity with carrier concentration in mid 10 17 cm -3 range and mobility of ~10 cm 2 /Vs. PL spectra of p-type ZnO:N films show a sharp peak at 3.36 eV, most likely due to neutral acceptor bound excitons. The transmittance of p-ZnO:N in the whole visible spectrum is ~ 80 % making it suitable for transparent electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Hydrogen is an impurity that can be present in ZnO made by many fabrication techniques [3,9,[23][24][25]]. An isolated interstitial H is predicted to be exclusively donor in ZnO, i.e., it always exists in the form of an H + and bonds with the host O atom [26].…”
Section: Impurity and Defect Complexes Analysismentioning
confidence: 99%
“…Hydrogen is an impurity that can be present in ZnO made by many fabrication techniques [3,9,[23][24][25]]. An isolated interstitial H is predicted to be exclusively donor in ZnO, i.e., it always exists in the form of an H + and bonds with the host O atom [26].…”
Section: Impurity and Defect Complexes Analysismentioning
confidence: 99%
“…Similarly Zn 3 N 2 nanoneedles have been prepared by Khan et al [10] and by Khan and Cao [11] who found an indirect energy band gap of 2.81 eV. In contrast, Zn 3 N 2 layers [12] have been studied in more detail, while p-type ZnO layers have been prepared by thermal oxidation of Zn 3 N 2 [13] which is important since ZnO is usually n-type due to oxygen defects. It should be noted, however, that p-type ZnO layers have also been obtained by nitrogen doping of ZnO using small flows of NH 3 [14,15], which is a topic of active interest since nitrogen is considered to be a shallow-like, p-type impurity in ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for high-quality ptype ZnO films to produce LEDs and LDs. There are reports on p-type ZnO films grown heteroepitaxially using molecular beam epitaxy (MBE), pulsed laser deposition (PLD), metal-organic chemical vapor deposition (MOCVD) and magnetron sputtering [1][2][3][4]. However, homoepitaxial growth of ZnO films seems to be best for obtaining high-quality films because of no mismatches of a lattice constant and a thermal expansion coefficient.…”
mentioning
confidence: 99%